The beneficial role of functional food components in mitigating ultraviolet‐induced skin damage. (30th January 2019) - Morifuji, Masashi
Abstract: Excessive exposure to ultraviolet (UV) radiation can chemically alter biological molecules and is one of the major environmental health risks with potential to damage the structure and function of the skin. Numerous dietary supplements are known to optimize the skin's defenses against radiation exposure. Several studies in which the beneficial roles of functional food components, that can protect against UV‐induced skin damage, have been demonstrated. Supplemental dietary sphingomyelin maintains covalently bound ω‐hydroxy ceramides to avert skin barrier defects after UVB irradiation. The oral administration of collagen hydrolysates has been shown to limit decreases in skin elasticity via increases in the dermal hyaluronic acid content. Milk fermented with lactic acid bacteria has been shown to augment DNA repair mechanisms and improve skin immunity in the aftermath of UVB damage. Furthermore, long‐term ingestion of fermented milk containing lactic acid bacteria, collagen hydrolysates and sphingomyelin increases the minimal erythema dose (MED) in human subjects with moderate sunburn or redness and tanned skin after exposure to UV solar radiation. Thus, products containing these functional food components are one means by which the adverse effects of UV radiation on the skin can be mitigated.